Spices and Tourism : Destinations, Attractions and Cuisines - Jolliffe, Lee (Channel View Publications, 2014)
This is the first book to explore the relationship between tourism and spices. It examines the various layers of connection between spices and tourism in terms of destinations, attractions and cuisines. The book reveals how spice-producing destinations are employing spices in destination branding and encouraging spice farms to move towards tourism, while destinations not producing spices are employing spices and herbs in distinctive local cuisines. Both tangible and intangible spice heritages are highlighted as tools for developing destinations, creating attractions, inventing new forms of liv.